Structural, optical, and electrical properties of tin iodide-based vacancy-ordered-double perovskites synthesized via mechanochemical reaction - Cho, Hanbyeol; Yun, Yeonghun; Choi, Won Chang; Cho, In Sun; Lee, Sangwook (Ceramics International, 2022)
Over the recent past, lead-based halide perovskite materials have drawn significant attention due to their excellent optical and electrical properties for solar cells and optoelectronics applications. However, the toxicity of lead elements and instability under ambient conditions leads to develop alternative compositions. Herein, we report a novel mechanochemical synthesis of tin iodide-based double perovskites (A2SnI6; A = Rb+, Cs+, methylammonium, and formamidinium), and their structural, optical, and electrical properties are investigated. Importantly, we found that the hydrogen iodide (HI) addition during the ball-milling process minimizes secondary phase formation in the synthesized A2SnI6 powders. The effects of HI addition and the A-site substitution are investigated with respect to the lattice parameters, optical bandgaps, and electrical properties of the synthesized perovskite materials. Our results demonstrate essential information to improve the understanding of halide perovskite materials and develop efficient lead-free perovskite photoelectric devices.
Keywords: Crystals structures; Halide perovskites; Lead-free perovskites; Mechanochemical reactions; Mechanochemical synthesis; Optical and electrical properties; Optoelectronic applications; Ordered double perovskites; Solar-cell applications; Synthesised; Crystal structure; Electrical properties; Lead-free perovskites; Mechanochemical synthesis; Optical properties